Associations Between Hormonal Biomarkers and Preterm Infant Health and Development During the First 2 Years After Birth. Issue 2 (April 2021) - Cho, June; Chien, Lung-Chang; Holditch-Davis, Diane
Background: Testosterone levels have been used to examine infant boys' vulnerability to health and developmental problems, following the general theories of gender differences and the theory of extreme male brain of autism. Objectives: As testosterone is a representative androgen hormone and is higher in preterm than full-term infants, we used this steroid to determine if hypothalamic pituitary hormones, testosterone, and cortisol, were related to physical growth, health, and development of very-low-birthweight (VLBW, BW < 1, 500 g) infants. Method: For this comparative longitudinal study, 40 VLBW infants were recruited from a neonatal intensive care unit of a tertiary medical center. Data were collected from medical record reviews, questionnaires, and assessments of infant development at 6, 12, and 24 months. We collected saliva at the three time points and measured hormones using enzyme-immunoassays. Results: General and generalized mixed models showed that a 1pg/ml increment of testosterone was related to a −0.42% decrease in body weight, a −0.18% decrease in length, and a −0.10% decrease in head circumference. Cortisol levels were not associated with any outcome variable. The interactions between testosterone and time on physical growth and socioemotional development also occurred. Discussion: Elevated testosterone levels can be a biological risk factor for poor infant growth and development. Theories about the effects of elevated prenatal testosterone could be useful in predicting health and developmental outcomes among VLBW infants. Research beyond the first 2 years will be needed as infants show more socioemotional and behavioral problems as they grow older.